Kebijakan Politik Pemerintahan Bojonegoro dalam Mengelola Sumber Daya Alam Minyak Bumi - Reny Yulianty; Diny Fitrhatin (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2020)
Bojonegoro is a district with abundant natural resources (petroleum) and has been exploited since the colonial era until now, but until 2008 Bojonegoro is still the poorest area in East Java. But after 2008 under the leadership of Suyoto, Bojonegoro improved in managing its Natural Resources for the greatest prosperity of its people. Among the developments carried out by the Bojonegoro Regency Government after 2008 can be seen from several development indicators which include: Economic Growth, Poverty Rate, Sustainable Development Goals (SDGs), Open Government Partnership (OGP). Bojonegoro is an example of the success of the Regional Government in managing Natural Resources in the Regional Autonomy Region. This can be an example for other autonomous regions in managing natural resource management policies for the greatest prosperity of the people.